Effect of Serial Passage on Growth Kinetics, Biological Properties, and Differentiation into Adipocytes of Human Wharton’s Jelly-Derived Mesenchymal Stem Cells - Rizal Rizal; Wahyu Setia Widodo; Satrio Wibowo; Ubaydillah Zedd Munshy (Majalah Kedokteran Bandung, 2019)
Early passges of human Wharton’s jelly-derived mesenchymal stem cells (hWJMSCs) have been suggested by various studies; however, the effect of serial passaging has not been well defined. This study aimed to investigate the effect of serial passage on the growth kinetics, biological properties and differentiation into adipocytes on hWJMSCs. This study was conducted from April to December 2014 to evaluate the hWJMSCs growth kinetics at passage 6 (P6) and P12 by calculating proliferation rate, population doubling time (PDT), and cumulative population-doubling levels (CPDL) using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium MTS assay kit. The cells biological properties were characterized using flow cytometry analysis followed by measuring the differentiation into adipocytes in extensive culture using Oil Red O staining after induction. An independent sample t-test was applied to analyze the differences between groups using IBM SPSS Statistics Version 22 with a p<0.05 considered significant. The growth kinetics assay showed the cells at P6 had a higher proliferation rate, CPDL, and faster PDT compared to the cells at P12 (p<0.05). Data from expression of MSCs surface markers showed that the cells retained their biological properties at both passages but decreased at P12 (p<0.05). The formation of intracellular lipid droplets was also observed at both passages under adipogenic induction. However, the content of oil red O extracted-cells decreased at P12 (p<0.05). The hWJMSCs decreased their growth kinetics, biological properties, and differentiation into adipocytes as a result of serial passage. This finding might be valuable for treating degenerative diseases using cell-based therapy. Pengaruh Pasase Berseri terhadap Kinetika Pertumbuhan, Karakteristik Biologis, dan Diferensiasinya Menjadi Adipocytes yang Berasal dari Jaringan Wharton’s Jelly-Sel Punca MesenkimPenelitian tentang sel punca mesenkim yang berasal dari jaringan Wharton’s Jelly manusia (hWJMSCs) hanya disarankan penggunaanya pada pasase awal. Pengaruh pasase berseri terhadap karakteristik sel hWJMSCs belum banyak diuraikan dengan baik. Penelitian ini bertujuan untuk mengetahui efek dari pasase berseri terhadap kinetika pertumbuhan, sifat biologis dan diferensiasi menjadi adipocytes dari sel hWJMSCs. Penelitian ini dilakukan di Laboratorium Fisiologi, Fakultas Kedokteran, Universitas Gadjah Mada dan Aretha Medika Utama, Biomolecular and Biomedical Research Center, dari bulan April sampai Desember 2014. Kinetika pertumbuhan sel hWJMSCs pada P6 dan P12 dievaluasi dengan menghitung laju pertumbuhan sel, population doubling time (PDT), dan cumulative population-doubling levels (CPDL) menggunakan uji MTS. Sifat biologis sel dikarakterisasi menggunakan flowsitometri dengan mengukur ekspresi penanda permukaan CD90, CD105, CD73, dan CD44. Kemampuan diferensiasinya menjadi adipocytes diukur menggunakan pewarnaan Oil Red O setelah induksi mendium diferensiasi adipogenik. Uji kinetika pertumbuhan sel menunjukkan sel-sel di P6 memiliki tingkat proliferasi dan CPDL yang lebih tinggi dan PDT yang lebih cepat dibanding dengan sel-sel P12 (p<0,05). Karakterisasi MSCs menunjukkan bahwa sel-sel tersebut mempertahankan sifat biologisnya di kedua pasase tetapi menurun pada P12 (p<0,05). Jumlah intraseluler lemak pada P12 lebih sedikit dibandingkan pada P6 (p<0,05). Kinetika pertumbuhan, sifat biologis, dan kemampuan berdiferensiasi menjadi adipocytes dari hWJMSCs menurun sebagai akibat pasase berseri.